PENGARUH PROBLEM BASED LEARNING MODEL DALAM PEMBELAJARAN RENANG GAYA DADA BAGI SISWA DI SMKN 1 RENGASDENGKLOK - Ahmad Faisal Mafahir; Rekha Ratri Julianti; Abdul Salam Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem Based Learning model in breaststroke swimming learning for students at SMKN 1 Rengasdengklok. This study uses an experimental method with a quantitative approach. The research design used is Pre-Experimental Design with a one-group pretest-posttest design. The research sample was selected using a systematic sampling technique. The instrument used was a breaststroke swimming ability test given before and after treatment. The pretest results showed an average value of 42.11, while the posttest results increased to 62,62. Hypothesis testing was carried out using a paired sample t-test, and a significance value (2-tailed) of 0.001 < 0.05. (Ho) is rejected and (Ha) is accepted. These results indicate that the Problem Based Learning model has a significant effect on improving students' breaststroke swimming ability.